Phase out tariffs, phase in trade? - Tibor Besedes; Tristan Kohl; James Lake (Center for Economic Studies and ifo Institute (CESifo), 2019)
What causes U.S. trade with Mexico and Canada to continue growing faster, for up to a decade, relative to countries with which the U.S. does not have a free trade agreement? Baier and Bergstrand (2007) suggest that tariff phase-out and delayed pass-through of tariffs into import prices could cause such prolonged differential import growth. We examine how tariff cuts negotiated under the Canada-US Free Trade Agreement and the North American Free Trade Agreement (NAFTA) affected U.S. import growth in 19892016 using detailed product-level data on tariff phase-out in the original treaties. We find essentially no evidence for the tariff phase-out or delayed pass through explanations. Rather, we find evidence for an important role played by NAFTA tariff cuts reducing the impacts of frictions at various extensive margins.
Keywords: F10; 330; free trade agreements; CUSFTA; NAFTA; trade; phase-out; tariffs; extensive margin